2011
DOI: 10.1007/s10096-011-1448-y
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses Streptococcus mutans adherence to human tooth surfaces and extracellular matrix proteins

Abstract: Streptococcus mutans is the key causative agent of caries and infective endocarditis. The first step in biofilm development and the consequent initiation of further disease is bacterial adherence to host cell surfaces. Therefore, the aim of this study was to evaluate the inhibitory effect of curcumin on S. mutans adherence to extracellular matrices and tooth surfaces. The effect of curcumin on the ability of S. mutans to adhere to glass surfaces coated with collagen and fibronectin was tested in order to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 25 publications
4
46
0
2
Order By: Relevance
“…Since it appears somewhat more soluble in DMSO than nCUR, aqueous solutions for oral application can be produced with less DMSO (i.e., 0.04% vs. 0.1%, vol/vol). In this context, it is worth mentioning that CUR has recently also been shown to inhibit adherence to teeth and extracellular matrix of Streptococcus mutans , the major causative agent of human caries [14,15]. In the present study we found that antimicrobial activity of sCUR in standard time-kill analyses was indistinguishable from nCUR [5,16,17] on a weight per volume basis for 3 major pharyngeal species (Figure  2).…”
Section: Discussionsupporting
confidence: 49%
“…Since it appears somewhat more soluble in DMSO than nCUR, aqueous solutions for oral application can be produced with less DMSO (i.e., 0.04% vs. 0.1%, vol/vol). In this context, it is worth mentioning that CUR has recently also been shown to inhibit adherence to teeth and extracellular matrix of Streptococcus mutans , the major causative agent of human caries [14,15]. In the present study we found that antimicrobial activity of sCUR in standard time-kill analyses was indistinguishable from nCUR [5,16,17] on a weight per volume basis for 3 major pharyngeal species (Figure  2).…”
Section: Discussionsupporting
confidence: 49%
“…The first critical step in the microbial colonization of host tissue is the adherence of bacteria to constituents of the host extracellular matrix, including fibronectin, laminin, and collagen (56,57). While many in vitro biofilm models have utilized host extracellular matrix factor-coated surfaces (e.g., collagencoated glass slides and collagen encapsulation to simulate biofilm) (58,59), the microbial biofilm dogma has historically considered only the role of the bacterium-derived matrix or EPS in antimicrobial tolerance. We found that being embedded in a matrix clearly protected S. aureus and P. aeruginosa from gentamicin.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial adhesion and subsequent biofilm formation (early biofilm formation) is the first step of pathogenic biofilm formation (Song et al , ; Friedlander et al , ). Hence, strategies to inhibit early biofilm formation by cariogenic bacteria may be an effective means to control the development of cariogenic biofilms.…”
Section: Discussionmentioning
confidence: 99%